CAN SPINAL ANAESTHESIA BE A ROUTINE FOR SINGLE LEVEL LUMBAR DISCECTOMY? Spinal Anaesthesia for Lumbar Discectomy - Hussain, Zahid; Ghaffar, Abdul; Mushtaq, Muhammad Junaid; Qasmi, Shahzad Ahmed (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the efficacy of spinal anaesthesia with general anaesthesia for lumbar discectomy in terms of theatre time and post-operative effects.Study Design: Randomized controlled trial.Place and Duration of Study: Neurosurgery department Combined Military Hospital Rawalpindi, from November 2013 to April 2014.Material and Methods: A total 60 consecutive patients with herniated lumbar discs were enrolled in this study to undergo randomly into assigned spinal anaesthesia group SA (n=30, group A) or General anaesthesia GA (n=30, group B).Variables included age, gender, level of lumbar disc prolapse, type of anaesthesia, operative time, and combined total theatre time, post-operative pain using visual analogue scale (VAS) and hospital stay in days.Results: Mean theatre time in group A was 62.70 and for group B it was 90.73 (p